Outcomes of Asthma Education: Results of a Multisite Evaluation - Wilma M Hopman; Nancy Garvey; Jennifer Olajos-Clow; Andrea White-Markham; M Diane Lougheed (Canadian Respiratory Journal)
BACKGROUND: This observational study compared the effectiveness of a standardized adult asthma education program administered in a variety of sites and practice settings on health care utilization, absenteeism, amount of leisure time missed and quality of life (using the Medical Outcomes Study 36-Item Short Form 1.0 [SF-36]).